Functional and radiological outcome of tibial plateau schatzker type v and type vi treated with dual plating - Rijal, Sanjeeb; Sitaula, Jyoti; Basel, Suman; Sharma, Bishnu Dev; Dawadi, Tej Prakash; Lohani, Suman (Journal of Chitwan Medical College, 2021)
Background: The bicondylar fractures are common fractures. These high energy fractures are most commonly associated with the various complications like malalignment, varus collapse, postoperative stiffness, wound complication. This study is aimed to assess the functional and radiological outcome and stability of dual plating for these fractures. Methods: This was a retrospective study which included 25 cases tibial plateau fractures Schatzker V and VI treated with dual plating from 1st January 2016 until 30th December 2019 in Chitwan Medical College Nepal.). These fractures were operated with anterolateral approach and medial approach and dual plating was done. The clinical outcome was evaluated using Rasmussens score and radiological evaluation was done by calculating MPTA, PPTA angle. Results: The functional outcome of our patients was assessed with Rasmussens functional score which showed excellent 15 (60%), good 9 (36%) and fair in 1 (4%) of the patient. The four cases had superficial infection. There was no secondary loss of reduction, malalignment in the study. The medial proximal tibial plateau angle (MPTA) of the injured and uninjured Limb had no significant statistical differences, however proximal posterior tibial plateau angle (PPTA) showed Significant difference p=0.025. Conclusions: The open reduction and Internal fixation with dual plating for bicondylar proximal tibia fracture is biomechanically efficient in preventing collapse and malalignment, however an accurate intraoperative reduction is the most important to achieve the alignment close to uninjured limb. The stable fixation allows early range of motion and rehabilitation and thus provide excellent to good functional outcome with minimal complication.